Das Auswärtige Amt in der NS-Diktatur - Mayer, Michael (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte, 2014)
This volume reviews research conducted surrounding the German Foreign Office and its past. What do we actually know about the function of the Foreign Office during the Nazi era, what gaps exist in the research, what is settled and what is under dispute? The authors seek to add additional context to the debate by discussing developments in research and changing views of historiography.